Aplikasi Akuntansi Pengolahan Transaksi Pendapatan Dan Belanja Daerah Berbasis Web - Eni Endaryati; Vivi Kumalasari Subroto; Sukemi Kamto Sudibyo (Universitas Sains dan Teknologi Komputer, 2024)
Computerized accounting is a system used to process company transaction data by using computers as a technological medium for application work processes and to produce financial reports for a company. The use and application of computer technology in office activities is a requirement and fairness that is needed, without having to eliminate manual systems. The use of computers will be able to improve employee performance in supporting activities in an agency or company. Financial management within the regional scope is the regional task and authority in organizing regional agencies which includes several sections including budgeting, income, expenditure, and accounting and accountability. The aim of this research is to design a web-based computerized accounting system for regional income and expenditure in Wates Village. And create a computerized accounting system that can assist the process of recording and storing web-based regional income and regional expenditure transaction data which produces regional income and expenditure report information. In creating a computerized system for regional income and expenditure, the software used is Sublime Texet3. Data storage uses MySQL and programming languages ​​use PHP and HTML. The research results show that the computerized accounting system makes it easier for finance employees to record financial transactions. Then financial reports are produced more quickly and data errors can be minimized and more structured data is stored in the database. So this new system really helps agencies in Wates Ngaliyan Village, Semarang, where the application is equipped with a menu for input, processes and reports that process transactions, both income and expenditure.